Handbook on product design and development basic fundamentals of industrial design - Millevo, Ronnie M. (Manila National Book Store, 1995)
This book aims to assist product designers and product designers-to-be, product managers, and students and teachers of Industrial Design in generating and processing new concepts for product innovation through various intuitive and logical approaches.
Provides a wide range of information about product design and development. Aids product designers and entrepreneurs in producing and developing new concepts and ideas for product innovation through various intellectual and strategic approaches.Gives step-by-step guides to material and product handling and processing, innovations, design illustration and creativity techniques.
Keywords: Design, Industrial -- Handbooks, manuals, etc